The Cartis Form for the Seismic Vulnerability Assessment of Timber Large-Span Structures - Beatrice Faggiano; Giacomo Iovane; Andrea Gaspari; Eric Fournely; AbdelHamid Bouchair; Raffaele Landolfo; Maurizio Piazza (Buildings, 2021)
Italy is located in a very active seismic zone, and many earthquakes have marked the country, some of them in the recent past. In order to take adequate measures of seismic prevention and protection, in the last decades, the Italian Civil Protection Department (DPC) initiated a survey and introduced a specific form for the quick and/or post-seismic assessment of buildings. This is useful to obtain statistics on the types of structures and their vulnerability and a judgement on the damage, leading to a decision about the possibility of reuse and/or the level of retrofitting to be applied. Those activities have been developed since the beginning of 2000. This task is currently carried out by the Italian DPC-ReLUIS project research, line WP2 on the inventory of building structures, setting up the CARTIS form for any structural type, like masonry, reinforced concrete, precast concrete, steel, and timber structures, the latter being mainly related to large span buildings, extensively used in Italy. In this context, the paper presents the first draft of the CARTIS form for large span timber structures that provides a general description for typical structural schemes, through the singular points commonly considered as seismic structural vulnerabilities. Moreover, the statistics on timber large span structures based on a sample of 10 buildings is presented.